Produktivitas Tenaga Kerja Sektor Pertanian dan Korelasinya dengan Usia Petani di Jawa Barat - Juri Juswadi; Pandu Sumarna (Lembaga Penelitian dan Pengabdian Universitas Winaya Mukti, 2023)
This study aims to determine the labor productivity of the West Java agricultural sector and its correlation with the age of the workforce. The research method is descriptive quantitative. The secondary data used in this study comes from the book State of the Labor Force Situation in Indonesia, 2013 to 2022 the results of the National Labor Force Survey (Sakernas) published by the Central Bureau of Statistics (BPS), and the book Jawa BaratÂ in Figures from 2008 to 2023 published by BPS West Java Province. The results showed: a) growth in labor productivity in the agricultural sector during the 2012-2022 period from IDR 22.29 million per worker per year in 2012 to IDR 31.56 million per worker per year in 2022; b) the largest number of workers starting sequentially is the age group of 45-54 years, age 35-44 years, age â‰¥ 60 years, and age 25-34 years, while the age group 15-24 years and age 55-59 years much lower; c) there was a decrease in the number of workers in the agricultural sector, except for the 55-59 year old group which an increase during the 2006-2017 period; d) the results of the Pearson correlation analysis show that there is a negative and significant correlation between labor productivity in the agricultural sector and the workforce in the 15-24 year old group (-0.821), 25-34 year old (-0.921), 35-44 year old (-0.948) ), and age 45-54 years (-0.848), while the workforce age group 55-59 years and age â‰¥ 60 is not related.